Differentiated Learning Innovation in Accommodating Students' Learning Needs at Daarul Aitam Middle School Palembang - Depi Elpiyanti; Reva Valianti; Heri Setianto (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aimed to analyze innovations in differentiated instruction for accommodating students' learning needs in Social Studies at SMP Daarul Aitam Palembang. A qualitative case study approach was employed involving one Social Studies teacher and 64 eighth-grade students selected through purposive sampling because they had implemented differentiated instruction under the Merdeka Curriculum. Data were collected through classroom observations, semi-structured interviews, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that diagnostic assessment serves as the foundation for designing differentiated content, processes, products, and learning environments according to students' readiness, interests, and learning profiles. The implementation of differentiated instruction increased students' participation, engagement, confidence, and learning motivation while creating a more inclusive and student-centered classroom environment. This study contributes to educational management and instructional innovation by demonstrating that diagnostic assessment is not merely an assessment tool but also a strategic basis for designing adaptive learning within the implementation of the Merdeka Curriculum.